Implementation of Group Counseling Services to Enhance Students' Self-Confidence Students at Integrated Islamic Junior High School Al Hijrah - Anggraini, Ayu; Lubis, Saiful Akhyar (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
Education is one of the efforts educators undertake to guide students towards maturity. However, this is often not accompanied by the necessary self-confidence among students, leading to negative impacts on the learning process. The objective of this research is to explore the implementation of group counseling services aimed at enhancing students' self-confidence at SMP IT Al-Hijrah. The research method employed is qualitative, utilizing data collection techniques such as interviews, observations, and documentation. The findings indicate that students' self-confidence increases after receiving group counseling services. Therefore, it can be concluded that group counseling services significantly enhance students' self-confidence in the learning process, particularly at SMP IT Al-Hijrah.